Artificial Intelligence Utilization in Supporting Da'wah Bil Kitabah Competency Among Islamic Communication and Broadcasting Students at UIN Sumatera Utara - Anggun Dwi Nanda Nasution; Rubino Rubino; Hasnun Jauhari Ritonga (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2026)
This study aims to analyze the use of artificial intelligence (AI) to support the da'wah bil kitabah competence of students of the Islamic Communication and Broadcasting (KPI) program at the Faculty of Da'wah and Communication. This study used a qualitative, descriptive approach, using data collection techniques such as in-depth interviews, observation, and documentation. The research informants were KPI students selected purposively. The results indicate that students are generally familiar with and use AI in academic activities, such as preparing assignments and searching for references. However, the use of AI in the context of da'wah bil kitabah remains relatively low. This is due to low interest and confidence in writing, the dominance of the oral da'wah paradigm, and a lack of encouragement from the academic environment. The findings of this study indicate a gap between the potential of AI as a writing aid and the reality of its use in da'wah bil kitabah activities. Therefore, strategic efforts are needed to increase student awareness and integrate technology into da'wah learning so that da'wah bil kitabah competence can develop optimally and be relevant to the digital era.